ACT NOW! A practical toolkit for amputation reduction. Issue Volume 33:Issue suppl 3(2022) (1st March 2022) - Robbie, Jayne; Edmonds, Mike; Phillips, Anne; Odiase, Charles; Beckwith, Anita; Diggle, Jane; Holmes, Patrick; Grummitt, John; Walker, Kate
Abstract : People living with diabetes are at risk of foot ulcers, leading to amputations. Jayne Robbie, in collaboration with the iDEAL group, discusses how ACT NOW can provide a practical toolkit to reduce amputations in this group Foot problems are often associated with multiple limb-threatening co-morbidities for people with diabetes. It has been suggested that many of these amputations could be avoided if foot ulcers are effectively detected, assessed, referred and rapidly treated in order to optimise healing. All health professionals in both primary and secondary care can have a pivotal role to play to reduce major amputations by 50%. Adopting ACT NOW and using this tool routinely, can reduce the unacceptably high volume of major amputations.